2021
DOI: 10.1590/1678-4685-gmb-2020-0390
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis reveals that mTOR pathway can be modulated in macrophage cells by the presence of cryptococcal cells

Abstract: Cryptococcus neoformans and Cryptococcus gattii are the etiological agents of cryptococcosis, a high mortality disease. The development of such disease depends on the interaction of fungal cells with macrophages, in which they can reside and replicate. In order to dissect the molecular mechanisms by which cryptococcal cells modulate the activity of macrophages, a genome-scale comparative analysis of transcriptional changes in macrophages exposed to Cryptococcus spp. was conducted. Altered expression of nearly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 79 publications
1
4
0
Order By: Relevance
“…This occurs by the deprivation of essential nutrients that hampers the pathogen development. Since amoebae and macrophages share antifungal mechanisms, and there are similarities in pathogenicity and behaviors between C. neoformans and C. gattii within the host ( Piffer et al, 2021 ; Derengowski et al , 2013 ), we hypothesize that amoeboid cells could also apply nutritional immunity as an antifungal strategy, as previously suggested by our group ( Ribeiro et al, 2017 ).…”
Section: Introductionsupporting
confidence: 58%
“…This occurs by the deprivation of essential nutrients that hampers the pathogen development. Since amoebae and macrophages share antifungal mechanisms, and there are similarities in pathogenicity and behaviors between C. neoformans and C. gattii within the host ( Piffer et al, 2021 ; Derengowski et al , 2013 ), we hypothesize that amoeboid cells could also apply nutritional immunity as an antifungal strategy, as previously suggested by our group ( Ribeiro et al, 2017 ).…”
Section: Introductionsupporting
confidence: 58%
“…After inhaled Cryptococcus cells are phagocytosed by alveolar macrophages, they alter the macrophage transcriptome, preventing significant acidification, calcium efflux and protease activity, and thereby allowing intracellular pathogen proliferation [ 51 ].…”
Section: Advances In Understanding Of Virulence and Pathogenesismentioning
confidence: 99%
“…Classically activated M1 macrophages that result from the usual Th1 cytokine immune profiles are essential for clearing Cryptococcus, while alternatively activated M2 macrophages resulting from Th2 cytokine stimulation are associated with a higher burden of disease [ 52 , 53 ]. C. gattii can modulate macrophage polarisation to M2, thereby evading immune recognition and clearance [ 51 , 52 , 53 ]. There are observed species-dependent in vitro differences in M1-polarised macrophage transcriptomic gene regulation and subsequent bioprocess modulation.…”
Section: Advances In Understanding Of Virulence and Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…TOR signalling in Cryptococcus has recently been shown to modulate the expression of genes required to aid pathogen survival in macrophages during infection. 56 As well as controlling TOR signalling at the vacuole membrane, Vps39 is part of the homotypic fusion and protein sorting (HOPS) complex required for the fusion of vesicles either derived directly from the Golgi, via the alkaline phosphatase (ALP) pathway, or indirectly from the late endosome, via the indirect vacuolar protein sorting (VPS) pathway, to the vacuole. 45 This study has shown that deletion of VPS39 in C. neoformans results in increased susceptibility to fluconazole, suggesting an essential role of membrane trafficking to the vacuole in the tolerance to antifungal drugs.…”
Section: Discussionmentioning
confidence: 99%